2023
DOI: 10.1021/acs.oprd.3c00218
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Process Development for the Biaryl Ether Fragment of Nemtabrutinib (MK-1026)

Nicholas R. Deprez,
Harrison B. Rose,
Byron K. Peters
et al.

Abstract: MK-1026, also known as nemtabrutinib (1), has been developed as a reversible Bruton's tyrosine kinase (BTK) inhibitor for the treatment of chronic lymphocytic leukemia. This article describes the two-step manufacturing synthesis and subsequent isolation of biaryl ether (4) en route to MK-1026. First, the esterification step employs unique conditions leveraging dimethyl carbonate as a dual-function reagent, acting as both the solvent and the desiccant to drive the reaction forward. Second, the heterogeneous eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nemtabrutinib is a reversible Bruton’s Tyrosine Kinase inhibitor developed for the investigational treatment of chronic lymphocytic leukemia . Development of the commercial route to nemtabrutinib through intermediate 5 has been reported, and is shown in Scheme . During the development of this process, it was found that 5 had a tendency to partition out of solution as an undesired oil phase during workup and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Nemtabrutinib is a reversible Bruton’s Tyrosine Kinase inhibitor developed for the investigational treatment of chronic lymphocytic leukemia . Development of the commercial route to nemtabrutinib through intermediate 5 has been reported, and is shown in Scheme . During the development of this process, it was found that 5 had a tendency to partition out of solution as an undesired oil phase during workup and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the reaction is quenched with aqueous acetic acid to arrive at the desired ketone ( 5 ). Additional processing steps outside the scope of this work are completed to arrive at the final active pharmaceutical ingredient, nemtabrutinib. …”
Section: Introductionmentioning
confidence: 99%